Evaluation of left ventricular systolic function by Myocardial Deformation Imaging in asymptomatic HIV patients - Sherpa, Kunjang; Sah, Ram Kishor; Maskey, Arun; Malla, Rabi; Sharma, Deewakar; Rajbhandari, Sujeeb; KC, Man Bahadur; Tamrakar, Rikesh; Shakya, Sushil; Timilsina, Birat Krishna; Hirachan, Anish; Koirala, Prabha Chapagain; et al. (Nepalese Heart Journal, 2019)
Background and Aims: Despite improvements in clinical care, evidence from both industrialized and developing countries indicates that the prevalence of subclinical cardiac dysfunction in individuals with well-controlled HIV infection may approach 50% and represent a newly recognized comorbid condition. The aim of our study was to reveal abnormalities in cardiac function using conventional transthoracic echocardiography and left ventricular strain imaging in HIV infected patients without cardiovascular disease.Methods: This was a hospital based, single center descriptive cross-sectional comparative study conducted in National Academy of Medical Sciences (NAMS), Bir Hospital which included HIV patients with baseline examination including a patient medical history, clinical examination, baseline CD4 count, viral load and a standardized transthoracic echocardiography and strain imaging examination and the findings were compared among age and sex frequency matched healthy adult population.Results: Our study enrolled 142 patients out of which 95 HIV positive patients (mean age 36.7±9.2 years with 58% female) and 47 healthy control (mean age 33.7±8 years with 57.4% female). The median duration of HIV diagnosis was 7 years (IQR 2, 10) and median CD4 count was 464 cells/mm3 (IQR 259,750). There was no significant difference in conventional echocardiographic parameters between two groups except for transmitral E velocity that was lower in HIV group (P value of 0.001). The HIV population has lower mean global longitudinal strain (GLS) value of -19.92% ± 2.54 SD compared to the healthy control population with mean of -21.39% ± 1.54 SD(P value of 0.001) and patients with CD4 count less than 300 cell/mm3 had GLS value significantly lower than -18% (P value of 0.05).Conclusion: HIV infected population without established cardiovascular disease have subclinical left ventricular dysfunction revealed by GLS imaging technique.